행정정보 데이터세트의 관리기준표 개선방안 연구 - 이정은(Jung-eun Lee); 김지혜(Ji-Hye Kim); 왕호성(Ho-sung Wang); 양동민(Dongmin Yang) (Journal of Records Management & Archives Society of Korea, 2022)
Administrative information datasets are a kind of record produced based on an organization's work performance. A dataset is evidence of the act of recording and contains a lot of information that can be used for work. Datasets have been neglected in Korea's records management system. However, as the law was revised in 2020, the management of administrative information datasets was legislated. Organizations that require management of administrative information datasets have already gradually begun record management. The core of managing administrative information datasets is the preparation of the Management Reference Table for the dataset. Regardless, there is confusion with the Records Management Reference Table for Dataset in institutions that work on records management, and it is difficult to work because the Management Reference Table for Dataset has a new concept. This study looked into the problems in the records management of datasets that appeared at the beginning of work. It isuggests a method to effectively settle records management for datasets. In that way, the Management Reference Table was selected as the research subject, and the problems discussed so far were summarized. In addition, the items of the current Management Reference Table were analyzed. As a result of the study, we have proposed the simplification of items in the Management Reference Table, the reorganization of areas in the Management Reference Table, the introduction of the concept of retention periods, and the preparation process of the Management Reference Table. 행정정보 데이터세트는 조직의 업무수행을 기반으로 생산되는 기록이다. 기록 행위에 대한 증거일뿐만 아니라 업무에 활용될 수 있는 수많은 정보를 포함하고 있다. 그동안 기록관리 현장의 그늘에 있던 데이터세트는 2020년 법령의 개정을 통해 기록으로 관리될 수 있는 법적 근거가 마련되었다. 이에 데이터세트 기록관리업무는 필요한 기관을 중심으로 이미 점진적으로 시작되었다. 데이터세트 기록관리업무의 핵심은 관리기준표의 작성에 있다. 그러나 기록관리를 수행하는 현장에서는 기록관리기준표 개념과의 혼선과 익숙하지 않은 개념의 등장으로 업무의 고충을 토로하고 있다. 본 연구는 이러한 배경 속에서 초반에 드러나는 데이터세트 기록관리의 문제점을 다시 한번 되짚어 보고, 보다 효과적으로 데이터세트 기록관리업무를 안착시킬 방법을 제시하고자 한다. 그 방안으로 관리기준표를 연구대상으로 선정하여 그간 논의되었던 문제점을 정리하고, 현행의 관리기준표 항목을 분석하였다. 연구의 결과로 관리기준표 항목의 간소화, 관리기준표 영역의 재편성, 보유기간의 개념 도입, 관리기준표 작성 프로세스를 제언하였다.